2020
DOI: 10.1002/rmv.2142
|View full text |Cite
|
Sign up to set email alerts
|

The role of endogenous retroviruses‐K in human cancer

Abstract: It is known that human endogenous retroviruses (HERVs) constitute almost 8% of the human genome. Although the expression of HERVs from the human genome is tightly regulated, different exogenous and endogenous factors could trigger HERV activation. Aberrant expression of different HERVs may potentially cause a variety of diseases such as neurological and autoimmune diseases as well as cancer. It is suggested that HERV-K can induce cancer through different mechanisms that are discussed. The interplay between som… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 147 publications
0
25
0
Order By: Relevance
“…Members of HERV-K that can replicate may cause disease if activated (Garcia-Montojo et al, 2018). In recent years, it was found that the abnormal expression of HERV-K protein and reverse transcriptional elements may lead to the development of pathological conditions (Qadir et al, 2017;Grandi and Tramontano, 2018;Küry et al, 2018;Matteucci et al, 2018;Kaplan et al, 2019;Alcazer et al, 2020;Curty et al, 2020;Salavatiha et al, 2020). HML-2 is the most active member of the HERV-K family and has the shortest time to integrate into the human genome.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Members of HERV-K that can replicate may cause disease if activated (Garcia-Montojo et al, 2018). In recent years, it was found that the abnormal expression of HERV-K protein and reverse transcriptional elements may lead to the development of pathological conditions (Qadir et al, 2017;Grandi and Tramontano, 2018;Küry et al, 2018;Matteucci et al, 2018;Kaplan et al, 2019;Alcazer et al, 2020;Curty et al, 2020;Salavatiha et al, 2020). HML-2 is the most active member of the HERV-K family and has the shortest time to integrate into the human genome.…”
Section: Introductionmentioning
confidence: 99%
“…RNA expression and protein products of HERV-K (HML-2) have been found in a variety of autoimmune diseases and malignancies (Evans et al, 2009;Serafino et al, 2009;Tai et al, 2009;Reiche et al, 2010;Downey et al, 2015;Küry et al, 2018;Matteucci et al, 2018;White et al, 2018;Levet et al, 2019;Alcazer et al, 2020;Curty et al, 2020;Salavatiha et al, 2020). Despite an increasing number of these reports, no causal relationship has been identified (Hurst et al, 2016;Qadir et al, 2017;Bannert et al, 2018;Matteucci et al, 2018;White et al, 2018;Kaplan et al, 2019;Levet et al, 2019;Curty et al, 2020;Salavatiha et al, 2020). Some pathological conditions may be related to the upregulation of RNA transcription of HERV-K (HML-2), the irregular expression of viral proteins and viral particles, or the production of autoantibodies against HERV-K ( Jones et al, 2012;Hurst et al, 2016;White et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, HERV-L shows elevated numbers of somatic single-nucleotide variations in cancer (68), which may impact cancer progression. In addition, HERVs are able to induce carcinogenesis and cancer progression by regulating nearby host genes (12,69,70). Herein we reported positive association between expression of some HERVs and their neighbor genes.…”
Section: Discussionmentioning
confidence: 51%
“…They play important physiological roles in early stages of human development but get silenced in adults [105]. However, expression in adult life has been associated with various cancers (reviewed in [106]), autoimmune diseases (reviewed in [107]), and neurodegenerative diseases [12,108,109]. Since multiple copies of these viral genes are scattered across the genome, they also potentially could recombine and form a replicating viral particle (reviewed in [110]).…”
Section: Viral Persistence By Integration Into the Genome And Formation Of Defective Virusesmentioning
confidence: 99%